# solve the equation:3x^2 +5x -12 = 0 using the formula.

*print*Print*list*Cite

### 2 Answers

Given the equation:

3x^2 + 5x -12 = 0

We need to solve for x.

We will use the formula to find the roots of the quadratic equations.

We know that:

x = [ -b +- sqrt(b^2-4ac)/ 2a

==> x1= ( -5 + sqrt(25-4*3*-12)]/2*3

= (-5 + sqrt(169) / 6

= (-5 +13)/6 = 8/6 = 4/3

==> x1= 4/3

==> x2= (-5 -13)/6 = -18/6 = -3

==> x2= -3

Then the solution for the quadratic equation is:

**x= { 4/3 , -3}**

3x^2 +5x -12 = 0

There is another way for solving quadratic equations i.e factorization

3x^2 +5x -12 = 0 can be factored as

for this we will be splitting the 5x in a way that the product of the parts is equal to the product of 3 and -12

3x^2+9x-4x-12=0

3x(x+3)-4(x+3)=0

(x+3)(3x-4)=0

so x=-3,4/3